Car country : an environmental history - Wells, Christopher W. (Weyerhaeuser environmental book., 2012)
For most people in the United States, going almost anywhere begins with reaching for the car keys. This is true, the author of this book argues, because the United States is Car Country - a nation dominated by landscapes that are difficult, inconvenient, and often even unsafe to navigate by those who are not sitting behind the wheel of a car. The prevalence of car-dependent landscapes seems perfectly natural to us in the twenty-first century, but it is, in fact, a relatively new historical development. Here, the author rejects the idea that the nation's automotive status quo can be explained as a simple byproduct of an ardent love affair with the automobile. Instead, he takes readers on a lively tour of the evolving American landscape, charting the ways that new transportation policies and land-use practices have combined to reshape nearly every element of the built environment around the easy movement of automobiles. From the dawn of the motor age to the establishment of the Interstate Highway System and the rise of the suburbs, the author untangles the complicated relationships between automobiles and the environment, allowing readers to see the everyday world in a completely new way. The result is a history that is essential for understanding American transportation and land-use issues. -- Book jacket.